2013
DOI: 10.2174/18715273112119990053
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxygenase: An Emerging Target for Stroke Therapy

Abstract: Neuroprotection as approach to stroke therapy has recently seen a revival of sorts, fueled in part by the continuing necessity to improve acute stroke care, and in part by the identification of novel drug targets. 12/15-Lipoxygenase (12/15-LOX), one of the key enzymes of the arachidonic acid cascade, contributes to both neuronal cell death and vascular injury. Inhibition of 12/15-LOX may thus provide multifactorial protection against ischemic injury. Targeting 12/15-LOX and related eicosanoid pathways is the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 124 publications
1
30
0
Order By: Relevance
“…[4][5][6] Inhibition of 12/15-LOX reduces infarct size, edema, and blood-brain barrier leakage, and is being investigated as a novel approach to stroke therapy. 3,[5][6][7][8] One of the key regulators of this redox homeostatic network, along with the hypoxia-inducible factors, is the Signal Transducers and Activators of Transcription (STAT) family of proteins. 9 Phosphorylation at specific tyrosine residues and subsequent dimerization is required for STAT activation; the dimers then translocate to the nucleus, where they bind to their target gene's promoter region.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Inhibition of 12/15-LOX reduces infarct size, edema, and blood-brain barrier leakage, and is being investigated as a novel approach to stroke therapy. 3,[5][6][7][8] One of the key regulators of this redox homeostatic network, along with the hypoxia-inducible factors, is the Signal Transducers and Activators of Transcription (STAT) family of proteins. 9 Phosphorylation at specific tyrosine residues and subsequent dimerization is required for STAT activation; the dimers then translocate to the nucleus, where they bind to their target gene's promoter region.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of m12/15-LOX is increased in the mouse brain following ischemic induction and m12/15-LOX co-localizes with a marker for oxidized lipids, MDA2. 4 In addition, a similar co-localization was detected in the brain of human stroke patients, as well as increased levels of apoptosis-inducing factor, AIF. 4,6 Finally, animal studies by van Leyen et al demonstrated a 40% reduction of infarct size in a m12/15-LOX knockout (K/O) mouse relative to wild-type (WT).…”
Section: 1 Introductionmentioning
confidence: 70%
“…4 In addition, a similar co-localization was detected in the brain of human stroke patients, as well as increased levels of apoptosis-inducing factor, AIF. 4,6 Finally, animal studies by van Leyen et al demonstrated a 40% reduction of infarct size in a m12/15-LOX knockout (K/O) mouse relative to wild-type (WT). 9 These data strongly suggest that h12/15-LOX is involved in stroke and might be an attractive therapeutic target.…”
Section: 1 Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…[10] Moreover, it has been shown that 15-LOX-1 is upregulated in mice following a stroke and the ensuing ischemia. [11] In addition, 15-LOX-1 has been linked to airway inflammation diseases[1216] such as asthma, chronic obstructive pulmonary disease (COPD) and chronic bronchitis, and more recently in various CNS diseases[11,1725] like Alzheimer’s and Parkinson’s diseases as well as stroke. Recent evidence shows that 15-LOX-1 plays conserved roles in the molecular mechanisms contributing to the pathophysiology of these diseases.…”
Section: Introductionmentioning
confidence: 99%